2016
DOI: 10.1080/10410236.2015.1069165
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of a Computerized Touch Screen Decision Aid to Increase Acceptance of Colonoscopy Screening in an African American Population with Limited Literacy

Abstract: The goal of this study was to assess the effectiveness of a touch screen decision aid to increase acceptance of colonoscopy screening among African American patients with low literacy, developed and tailored using perceptual mapping methods grounded in Illness Self-Regulation and Information-Communication Theories. The pilot randomized controlled trial investigated the effects of a theory-based intervention on patients’ acceptance of screening, including their perceptions of educational value, feelings about c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…There was lack of indebtedness that genomic tests would not reveal information about heritable traits, raising the question whether misunderstanding of the terms among those concerned with reveling information about heritable traits could influence their acceptance of such testing. Considering the extant-literature emphasis on patient education to improve health literacy 19,20 and the interest expressed by this study’s participants in becoming better educated about genomic testing, improvement of patient-centered education is essential. Decision aids have been shown to effectively provide concise education about complex medical issues, including PSA testing, 21,22 and could possibly be applied to genomic testing.…”
Section: Discussionmentioning
confidence: 99%
“…There was lack of indebtedness that genomic tests would not reveal information about heritable traits, raising the question whether misunderstanding of the terms among those concerned with reveling information about heritable traits could influence their acceptance of such testing. Considering the extant-literature emphasis on patient education to improve health literacy 19,20 and the interest expressed by this study’s participants in becoming better educated about genomic testing, improvement of patient-centered education is essential. Decision aids have been shown to effectively provide concise education about complex medical issues, including PSA testing, 21,22 and could possibly be applied to genomic testing.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these methods can help target messages to the specific needs of a population, as a commercial entity might market a product to a consumer. This is unique to the development of public health social marketing interventions and has been shown in other studies by the authors to be effective (Bass et al, 2013;Ruzek et al, 2016;Jessop et al, 2019).…”
Section: Discussionmentioning
confidence: 64%
“…This finding regarding trust is in line with previous research. Positive source attribution has also been demonstrated as being associated with increased intentions to seek additional cancer information, to share information, and to intend to screen for cancer -all important cognitive precursors to actual cancer screening (Ruzek et al, 2016). In fact, Nivens et al (2001) found that among a predominantly African American study population, receiving information from a trusted health source was more strongly associated with increased prostate screening than any other kind of predictor.…”
Section: Discussionmentioning
confidence: 99%